Actions mondiales pour un pastoralisme et des parcours durables afin d'atteindre la Neutralité en matière de Dégradation des Terres - Louhaichi, Mounir; Masumbuko, Bora; Niamir-Fuller, Maryam; Herrera, Pedro; Liniger, Hanspeter; Mekdaschi-Studer, Rima; Bendandi, Barbara Bendandi; Turin, Cecilia; Magero, Chris; Chavez, Eric; Haddad, Fidaa; Badripour, Hossein; et al. (International Year of Rangelands and Pastoralists, 2024)
Policy Brief (French) with Recommendations for the UNCCD Conference of the Parties (COP) Prepared by the IYRP Rangelands & Land Degradation Neutrality Working Group: Rangelands, which cover over half of the world's land surface, are essential for achieving Land Degradation Neutrality (LDN) and advancing global objectives such as the Sustainable Development Goals (SDGs). Despite their critical role, these ecosystems and the pastoralist communities who manage them remain underappreciated, facing significant threats from uncontrolled land conversion, poor governance, and chronic underinvestment. This policy brief, prepared by the IYRP Rangelands & Land Degradation Neutrality Working Group, calls for stronger global commitments to halt rangeland degradation, enhance sustainable pastoralism, and set LDN targets specific to rangelands. It outlines eight key actions, including stopping indiscriminate land conversion, recognizing pastoral mobility, strengthening participatory governance, and increasing financial support for rangeland projects under the LDN Fund. By adopting these recommendations, the UNCCD Conference of the Parties (COP) can play a pivotal role in preserving rangelands, promoting sustainable pastoralism, and contributing to climate resilience and biodiversity conservation, all while supporting the livelihoods of pastoralist communities.